2016
DOI: 10.5530/pj.2016.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Fraction from Datura stramonium Linn. Promotes Human immune Cells Mediated Cytotoxicity towards Lung and Breast Cancer Cells

Abstract: Aim: The aim of the present study was to evaluate immune modulatory effect of fractions of D. stramonium L. leaves on human peripheral blood mononuclear cells (PBMC) followed by assessment of cytotoxic abilities of immunomodulated PBMC toward cancer cells. Material and methods: Bioassay (PBMC proliferation) guided fractionation of methanolic leaf extract of D. stramonium was performed to get active fraction and LC-MS was performed to identify the phytocompounds present in the bioactive fraction. The immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…These findings were similar to those reported by Gupta et al [56], who investigated the cytotoxic effects of methanolic extracts of D. stramonium leaves on A549 and MCF7 cells, finding considerable immunostimulation [57]. The methanolic leaf extract of D. innoxia revealed a possible cytotoxic impact on MCF-7 human breast cancer cell lines, with an IC50 of 93.73 g/ml [57].…”
Section: Cytotoxic Activitysupporting
confidence: 88%
“…These findings were similar to those reported by Gupta et al [56], who investigated the cytotoxic effects of methanolic extracts of D. stramonium leaves on A549 and MCF7 cells, finding considerable immunostimulation [57]. The methanolic leaf extract of D. innoxia revealed a possible cytotoxic impact on MCF-7 human breast cancer cell lines, with an IC50 of 93.73 g/ml [57].…”
Section: Cytotoxic Activitysupporting
confidence: 88%
“…These results were like those exposed by Gupta et al [95] where the cytotoxic effects of methanolic extracts of D. stramonium leaves against A549 and MCF7 were evaluated, presenting a significant immunostimulation [94]. D. innoxia methanolic leaf extract showed a potential cytotoxic effect on MCF-7 cell lines of human breast cancer with an IC50 of 93.73 µg/ml [94].…”
Section: Cytotoxic Activitysupporting
confidence: 79%
“…This is the first report describing the immunoenhancing potential of the D. oil which could be due to the bioactive molecules present in the essential oil. Previously, it had been shown that D. stramonium leaves extract exhibited immunostimulatory potential on human lymphocytes (Gupta et al 2016).…”
Section: Immunomodulatory Activity Of D Oilmentioning
confidence: 99%